2021
DOI: 10.3390/healthcare9050526
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of College Students’ Physical Activity Level on Depression and Personal Relationships

Abstract: Background: Physical activity greatly affects human physical and mental health. This study investigated the effect of college students’ physical activity levels on depression and personal relationships. Methods: Participants were 525 college students from five Korean cities. The International Physical Activity Questionnaire, Beck’s Depression Inventory, and Leary’s interpersonal orientation paper test measured physical activity volume, depression, and interpersonal relationships, respectively. Data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
9
1
2
Order By: Relevance
“…Furthermore, Kim, Song, and Jeon (2021) reported that college students in the lowintensity physical activity group showed the most severe level of depression, followed by the high-intensity physical activity group; the least severe depression was found in the medium-intensity physical activity group [43]. The results of previous studies are inconsistent with the results of this study, and we need to explore the reason for this.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, Kim, Song, and Jeon (2021) reported that college students in the lowintensity physical activity group showed the most severe level of depression, followed by the high-intensity physical activity group; the least severe depression was found in the medium-intensity physical activity group [43]. The results of previous studies are inconsistent with the results of this study, and we need to explore the reason for this.…”
Section: Discussioncontrasting
confidence: 76%
“…The theoretical model of the psychological benefits of physical exercise suggests that physical exercise can directly influence behavioral performance, such as interpersonal interactions ( Tomporowski et al, 2011 ). Some studies have found that individuals who regularly participate in physical exercise are more likely to have improved interpersonal relationships ( Kim et al, 2021 ), consistent with the concept proposed by this theoretical model. Thus, interpersonal relationships may mediate the pathway by which physical exercise influences middle school students’ social adjustment.…”
Section: Introductionsupporting
confidence: 76%
“…Similarly, a longitudinal study of Canadian adolescents observed lower symptoms of depression among sports teams [12]. Physical activity improves mental and physical health, generates positive perceptions, and enhances psychological well-being [13].…”
Section: Introductionmentioning
confidence: 92%